2021
DOI: 10.25061/2527-2675/rebram/2021.v24i3.1055
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes embalagens no armazenamento de doce em massa de araçá amarelo (Psidium cattleianum Sabine) adoçado com xilitol

Abstract: O estudo da estabilidade de novos produtos oriundos do processamento de frutas nativas subutilizadas é essencial para o desenvolvimento da indústria nacional. O objetivo foi avaliar o efeito de diferentes embalagens sobre a estabilidade físico-química de doce em massa de araçá amarelo adoçado com xilitol. A polpa de araçá foi avaliada quanto aos parâmetros físico-químicos de qualidade e seguiu para o processamento do doce. O doce foi elaborado com 60% de polpa, 40% de xilitol, 2% de pectina de Baixo Teor de Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…The RDC 726 of July 1, 2022, which regulates the health requirements for edible mushrooms, fruits, and plant products, does not establish a maximum moisture limit in mass candies made from fruits (Brasil, 2022b). The moisture level found in bocaiuva mass candy was 32.16 g 100 g -1 , close to the reported value of 33.50 g 100 g -1 by Vieira et al (2021) in yellow araçá (Psidium cattleyanum Sabine, a guava-like berry) mass candy. Moisture is directly related to shelf life since increased water content favors the development of microorganisms (Sarantopoulos et al, 2001); nevertheless, that was not observed in the product, mainly due to the low pH of the candy and the processing under high cooking temperatures.…”
Section: Centesimal Compositionsupporting
confidence: 84%
See 1 more Smart Citation
“…The RDC 726 of July 1, 2022, which regulates the health requirements for edible mushrooms, fruits, and plant products, does not establish a maximum moisture limit in mass candies made from fruits (Brasil, 2022b). The moisture level found in bocaiuva mass candy was 32.16 g 100 g -1 , close to the reported value of 33.50 g 100 g -1 by Vieira et al (2021) in yellow araçá (Psidium cattleyanum Sabine, a guava-like berry) mass candy. Moisture is directly related to shelf life since increased water content favors the development of microorganisms (Sarantopoulos et al, 2001); nevertheless, that was not observed in the product, mainly due to the low pH of the candy and the processing under high cooking temperatures.…”
Section: Centesimal Compositionsupporting
confidence: 84%
“…The lipid content was 0.98 g 100 g -1 , superior to 0.40 g 100 g -1 reported by Vieira et al (2021) for the abovementioned araçá mass candy. That difference can be attributed to the high lipid content in bocaiuva pulp, which is composed mainly of monounsaturated fatty acids with a higher concentration of oleic acid (Amaral et al, 2019), or approximately 62% of the total extracted oil (Munhoz et al, 2012).…”
Section: Centesimal Compositioncontrasting
confidence: 64%
“…Various species of the Myrtaceae family, when processed, provide important products, such as essential oils, dyes, and food products, and can be also employed in traditional medicine [ 8 , 9 , 10 , 11 ]. This medicinal potential has been experimentally proven and associated with anti-rheumatic, antidiabetic, antimicrobial, diuretic, and digestive system regulatory activities, among others health beneficial activities, and has been evaluated in different experimental models both in vitro and in vivo [ 5 , 6 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food technology allows the incorporation of araçá into a multitude of products in order to make it available on the market, and it is found in the form of sweets, jams, and flour, benefiting producers and adding economic value to certain communities [ 20 ]. In scientific study, araçá was used in the development of jams [ 20 ], yoghurts [ 21 ], chewable bullets [ 22 ], and bulk candy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%